A Journey of Embedded and Cyber-Physical Systems : Essays Dedicated to Peter Marwedel on the Occasion of His 70th Birthday /: Essays Dedicated to Peter Marwedel on the Occasion of His 70th Birthday. (2020) - Unknown
No abstract available